2017
DOI: 10.1136/bcr-2017-221614
|View full text |Cite
|
Sign up to set email alerts
|

Ischaemic pituitary tumour apoplexy and concurrent meningitis: a diagnostic dilemma

Abstract: Pituitary tumour apoplexy is a rare but potentially life threatening clinical syndrome that mostly results from haemorrhage in the pre-existent tumour. Pure ischaemic subtype of apoplexy is even rarer. The presentation can be hard to differentiate clinically from bacterial meningitis. Moreover, the presence of one does not necessarily exclude the other and early diagnosis of both conditions is imperative for timely management. We report a case of ischaemic pituitary tumour apoplexy that may have precipitated i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…Asymptomatic pituitary apoplexy is frequently referred to as “subclinical pituitary apoplexy” in the medical literature 8 . The risk factors identified in various other studies and case reports are shown in the chart 9,10 . In our case, we suspected bacterial meningitis was a precipitating factor for pituitary apoplexy.…”
Section: Discussionmentioning
confidence: 57%
See 2 more Smart Citations
“…Asymptomatic pituitary apoplexy is frequently referred to as “subclinical pituitary apoplexy” in the medical literature 8 . The risk factors identified in various other studies and case reports are shown in the chart 9,10 . In our case, we suspected bacterial meningitis was a precipitating factor for pituitary apoplexy.…”
Section: Discussionmentioning
confidence: 57%
“… 8 The risk factors identified in various other studies and case reports are shown in the chart. 9 , 10 In our case, we suspected bacterial meningitis was a precipitating factor for pituitary apoplexy.…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…Pituitary apoplexy is known to present with chemical meningitis and, rarely, may present concurrently with bacterial meningitis, which itself has been suspected to precipitate PA. [4][5][6][7][8][9] Pituitary apoplexy has, infrequently, even been misdiagnosed as bacterial meningitis 7,8 due to a very similar clinical picture. Cerebrospinal fluid findings such as pleocytosis and erythrocytosis are nonspecific in cases of PA with suspected meningitis, with demonstration of bacteria in CSF being a key finding in distinguishing between chemical and pyogenic meningitis.…”
Section: Discussionmentioning
confidence: 99%